LIETUVOS FILOSOFINIŲ DISCIPLINŲ APŽVALGOS IR JŲ NARATYVINĖS STRATEGIJOS. - Gedutis, Aldis (Problems / Problemos, 2011)
The article applies the approach of sociology of philosophical knowledge in order to analyze the strategies Lithuanian philosophers use reviewing development of their disciplines. Four reviews on different fields of Lithuanian philosophy are analyzed: History of Lithuanian Philosophy (1993), Philosophical Studies of antiquity (1995), Phenomenology (2008), analytic Philosophy of Language and Science (2010). The major questions are to be answered: How development of certain philosophical field is described and presented? What role the references to external and extra-philosophical context play? What historical approach is predominant -- internal or external? What philosophers and texts are presented as most influential? What is dynamics of the philosophical texts presented in reviews?